The Role of Virtual Platforms in Shaping Contemporary Islamic Education - Shehar Bano; Mohamed Iyas Valarthodi (Al-Fadlan: Journal of Islamic Education and Teaching, 2025)
with personal mentorship as traditional learning methods. The swift technological progress has dramatically reshaped Islamic learning because it created extensive educational accessibility through digital platform usage together with remote Video classes and Artificial Intelligence educational resources. The research investigates how digital education affects Islamic learning while reviewing its present state along with its future perspective and associated hurdles. Research data collection relies heavily on qualitative techniques that utilize literature reviews combined with studies of prominent digital Islamic learning platforms which include Bayyinah Institute, Al-Maghrib Institute, Seekers Guidance and Islamic Online University. The research analyses the levels of credibility and accessibility while also evaluating engagement factors between digital learning in Islam versus traditional classroom techniques. The existing body of research about Islamic education still leaves a huge space to understand how digital learning affects students in multiple dimensions including their commitment and scholar authenticity when paired with their access to technology in disadvantaged communities. The research on conventional learning structures prevails over studies investigating the impact of online education in the existing academic field. The research establishes a bridge by performing an extensive evaluation of digital Islamic education benefits and weaknesses. Research takes place because digital education platforms have become essential for religious instruction particularly when used by Muslim minorities residing outside Muslim countries and self-directed learners who need flexible learning options. Investing knowledge into the effects these digital tools possess on religious education and scholarly communication will determine upcoming educational guidelines. The research demonstrates that virtual platforms bring many benefits to students, yet students must contend with issues of authenticity and insufficient mentorship along with ideological problems. Combining traditional madrasa education with digital methods creates the best learning system to preserve academic depth of traditional Islamic education through new technological resources. Research adds to academic knowledge by demonstrating the necessity to develop better authentication systems alongside increased digital education skills and joint ventures between traditional Islamic centres and virtual learning environments. Experts should research how digital Islamic education affects individuals psychologically and socially throughout time and how AI technology impacts the customization of Islamic religious content.